2020
DOI: 10.3390/ma13194331
|View full text |Cite
|
Sign up to set email alerts
|

Mixture Optimization of Recycled Aggregate Concrete Using Hybrid Machine Learning Model

Abstract: Recycled aggregate concrete (RAC) contributes to mitigating the depletion of natural aggregates, alleviating the carbon footprint of concrete construction, and averting the landfilling of colossal amounts of construction and demolition waste. However, complexities in the mixture optimization of RAC due to the variability of recycled aggregates and lack of accuracy in estimating its compressive strength require novel and sophisticated techniques. This paper aims at developing state-of-the-art machine learning m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(20 citation statements)
references
References 94 publications
0
20
0
Order By: Relevance
“…In 2020, Nunez I. et al [ 41 ] presented a study in which they built a machine learning model to predict the recycled aggregate concrete compressive strength and optimize the concrete mix design process. A reliable optimization method for concrete mix design is especially significant for recycled aggregate concrete, due to its variability and lack of proper compressive strength estimation formulas.…”
Section: Concrete MIX Design and Machine Learningmentioning
confidence: 99%
“…In 2020, Nunez I. et al [ 41 ] presented a study in which they built a machine learning model to predict the recycled aggregate concrete compressive strength and optimize the concrete mix design process. A reliable optimization method for concrete mix design is especially significant for recycled aggregate concrete, due to its variability and lack of proper compressive strength estimation formulas.…”
Section: Concrete MIX Design and Machine Learningmentioning
confidence: 99%
“…In the last few years, many researchers have developed different prediction models to estimate the compressive strength of eco-friendly concrete [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. To build a prediction model for the CS that contains RAC, two types of hybridized machine learning methods (an interval type-2 fuzzy inference system (IT2FIS) and type-1 fuzzy inference system (T1FIS)) were used [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The results reveal that the suggested ICA-XGBoost model outperformed the other models. In this study [ 17 ], RAC compressive strength and its optimal mixture design were predicted by machine learning models. The results demonstrated that the generated models, including deep learning, Gaussian processes, and gradient boosting regression, obtained reliable predictive performance, with the gradient-boosting regression trees outperforming the others.…”
Section: Introductionmentioning
confidence: 99%
“…In this way, the input dataset is split in two groups during the learning process (training and validation datasets), allowing the validation dataset to evaluate the DL model after its learning process on the retained input dataset in order to give more robustness to the DL model in its later use in similar input dataset and same target task (i.e., to avoid overfitting). However, in unsupervised learning, the DL model must be able to find natural groupings or structures within the input dataset (in a process known as clustering) or to reduce the input dataset dimensionality (procedure known as dimensionality reduction) without example input–output pairs [ 35 , 36 ]. Then, the task assigned is more specific when it is defined as supervised learning (e.g., estimating house prices from the values of surface areas, year of construction and location; or classifying images according to the animal species contained from a dataset acquired in a protected natural space), and more general when it is defined as unsupervised learning (e.g., grouping the DNA sequence of different patients in different categories in order to detect some genetic abnormality; or reducing the information contained in a point cloud for the elimination of noise and thus obtain a better 3D representation of the environment under study).…”
Section: Introductionmentioning
confidence: 99%